2016
DOI: 10.1080/1059924x.2016.1178612
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders and Agricultural Risk Factors Among Korean Farmers

Abstract: Farming is a strenuous occupation with various health risks, with musculoskeletal disorders (MSDs) being some of the most common. The risk factors for MSDs among Korean farmers are not well understood. Data were obtained from the Korean Farmers' Occupational Disease and Injury Survey (2012), which interviewed 16,113 participants regarding their demographic profiles, self-reported MSDs, and agricultural characteristics. Multiple logistic regression analysis was used to identify the risk factors for MSDs. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…8 In a survey of Southeast Kansas farmers [9], nearly 60% of the respondents reported that they experienced a farm work-related MSD symptom during the last 12 months, while a survey of selfreported work-related illness in Britain during 1995 found that 43 000 or 7% of the agriculture workforce ascribed MSDs to their work [10]. Evidence shows that agriculture type, years of farming, and ergonomic factors increased the risk of MSDs among Korean farmers [1]. A cross-sectional analysis was conducted using baseline survey data from the Saskatchewan Farm Injury Cohort Study and showed that most common MSD site in farmers was the low back followed by the upper and then lower extremities [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a survey of Southeast Kansas farmers [9], nearly 60% of the respondents reported that they experienced a farm work-related MSD symptom during the last 12 months, while a survey of selfreported work-related illness in Britain during 1995 found that 43 000 or 7% of the agriculture workforce ascribed MSDs to their work [10]. Evidence shows that agriculture type, years of farming, and ergonomic factors increased the risk of MSDs among Korean farmers [1]. A cross-sectional analysis was conducted using baseline survey data from the Saskatchewan Farm Injury Cohort Study and showed that most common MSD site in farmers was the low back followed by the upper and then lower extremities [2].…”
Section: Discussionmentioning
confidence: 99%
“…Farming is a physically effortful task which has various health risks and musculoskeletal disorders/discomfort being some of the most common [1]. Farmers are playing vital role in our national economy because they are providing food for us.…”
Section: Introductionmentioning
confidence: 99%
“…Keselamatan dapat dilakukan dengan mendefinisikan sikap dan posisi kerja yang benar, meminimalkan gerakan berulang serta mencegah gangguan muskuloskeletal (Bush, 2012). Menurut Kang, et al (2016) faktor risiko muskuloskeletal disorders (MSDs) sangat berkaitan erat dengan ergonomi. Muskuloskeletal Disorders adalah cedera dan penyakit pada otot, tendon, ligamen, sendi, saraf, pembuluh darah dan semua struktur yang terlibat dalam gerakan (Das & Gangopadhyay, 2014).…”
Section: Pendahuluanunclassified
“…It was noteworthy that even participants under 25 year olds reported musculoskeletal discomfort with the percentage reaching 81%. Finally, Kang et al [77] interviewed 16,113 Korean farmers concerning their agricultural characteristics, demographic profiles, and self-reported musculoskeletal discomfort with the use of specific questionnaires. Participants reported pain on the back (26.9%), lower extremities (19.62%), and on the regions of neck or muscles of the upper limbs (5.89%).…”
Section: Various Agricultural Tasksmentioning
confidence: 99%